Foundations of behavioral research - Kerlinger, Fred N. (Holt, Rinehart and Winston, 1964)
This book introduce the language and approach of science. Sets, relations and varriance. Analysis, interpretation, statistics and inference. Analysis of variance. Methods of observation and data collection...